Aplikasi Geometric Brownian Motion dengan Jump Diffusion dalam Memprediksi Harga Saham Liquid Quality 45 - Prilia Ditasari; Embay Rohaeti; Isti Kamila (Universitas Negeri Gorontalo, 2022)
At the beginning of 2021, stock LQ45 experienced a significant spike in stock prices, making the stock price difficult to predict and the profits obtained by investors uncertain. The purpose of this study is to predict the stock price of LQ45 using the Geometric Brownian Motion model with Jump Diffusion and determine investment by comparing the expected return and return of stock price prediction results. This study uses a Geometric Brownian Motion model with Jump Diffusion to predict stock prices because it can predict when stock prices experience price spikes and fluctuations. Based on the results of the study, of the 45 stocks listed on LQ45 stock, only nine stock companies were selected that had a normally distributed return whose stock price was predicted by applying the Geometric Brownian Motion model with jump-diffusion and each MAPE value obtained was in the very good category. There are six stock companies with investment decisions in the form of buying shares, including Ace Hardware Indonesia Tbk, Bank Central Asia Tbk, Charoen Pokphand Indonesia Tbk, Indofood CBP Sukses Makmur Tbk, Vale Indonesia Tbk and Indah Kiat Pulp Paper Tbk. Three stock companies with investment decisions in the form of selling shares including, Bank Rakyat Indonesia (Persero) Tbk, Jasa Marga (Persero) Tbk and Mitra Keluarga Karyasehat Tbk.